A field evaluation of sodium silicate and Bacillus subtilis on the growth and yield of banana following Fusarium wilt disease infection - Zakaria, Md Aiman Takrim; Sakimin, Siti Zaharah; Ismail, Mohd Razi; Ahmad, Khairulmazmi; Kasim, Susilawati (Multidisciplinary Digital Publishing Institute, 2022)
A field investigation was conducted in a Fusarium-infected area to evaluate the effectiveness of silicate compounds with antagonist bacteria on morpho-physiological growth performance in bananas. The roots of banana plants were treated by drenching the soil with four different treatments: control (without any treatment), CBZ (Carbendazim fungicide alone), SS + BS (integration sodium silicate with Bacillus subtilis), and CBZ + SS + BS (integration CBZ, SS, and BS). All treatments were arranged in a randomized complete block design with four replications. The results confirm that plant height, pseudo-stem diameter, and canopy diameter markedly increased from weeks 2 to 10 after transplantation. Amendment with these elements induced a higher total chlorophyll content, which contributed to the increased rate of leaf gas exchange and biochemical changes for controlling Fusarium wilt disease infection. From these findings, the CBZ + SS + BS application in the farm had significantly reduced disease incidence by 16.07% and disease severity by 14.28%. The same treatment achieved the greatest disease reduction by 63.05%. Therefore, the integration between CBZ + SS + BS had good significant effects in controlling Fusarium wilt disease and enhanced the morpho-physiological growth performance with an average yield production of about 24.72 kg per fruit bunch.